rewrite the polynominal (x+8)(x-2)

1 answer

To rewrite the polynomial \((x + 8)(x - 2)\), we can use the distributive property (also known as the FOIL method for binomials):

\[ (x + 8)(x - 2) = x \cdot x + x \cdot (-2) + 8 \cdot x + 8 \cdot (-2) \]

Now, calculate each term:

  1. \(x \cdot x = x^2\)
  2. \(x \cdot (-2) = -2x\)
  3. \(8 \cdot x = 8x\)
  4. \(8 \cdot (-2) = -16\)

Now, combine all the terms together:

\[ x^2 - 2x + 8x - 16 = x^2 + 6x - 16 \]

Thus, the rewritten polynomial is:

\[ x^2 + 6x - 16 \]